Comprehensive Characterization of the Algarve Octopus, Octopus vulgaris: Nutritional Aspects and Quality Indexes of Lipids - Ana G. Cabado; Celina Costas; David Baptista de Sousa; João Pontes; Mafalda Rangel (Applied Sciences)
The common octopus (Octopus vulgaris) supports one of the most valuable small-scale fisheries in Portugal, particularly in the Algarve region, with substantial socioeconomic implications. This species holds significant potential for human consumption due to its low lipid content, favorable fatty acid profile, high-quality protein, and essential microelements. This study aimed to provide a comprehensive characterization of octopus specimens landed in two key Algarve fishing areas—Barlavento/Windward (Alvor Harbour) and Sotavento/Leeward (Fuzeta Harbour). We assessed their nutritional value, focusing on protein quality, lipid indexes, trace minerals, and essential vitamins, as well as overall safety and quality. All regulated contaminants and additional potential risks were also evaluated, yielding fully satisfactory safety results. The research was conducted within the framework of the European Sea2See project, which aims to enhance consumer trust and acceptance of sustainably harvested or farmed seafood in Europe. Our findings demonstrate that Algarve octopus is a nutritionally rich seafood product, promoting cardiovascular health and general well-being.